ENTREPRENEURSHIP KNOWLEDGE, FAMILY SUPPORT, AND ENTREPRENEURIAL MOTIVATION ON THE INTEREST IN BECOMING YOUNG ENTREPRENEURS AMONG UKI TORAJA FACULTY OF ECONOMICS ALUMNI - Rahma Gusmawati Tammu; Olivia Devi Yulian Pompeng (SEAN Institute, 2023)
This study aims to examine the correlation between entrepreneurship knowledge, family support, and entrepreneurial motivation, and the interest in becoming young entrepreneurs among the alumni of the Faculty of Economics at UKI Toraja. A sample of 51 alumni who have already initiated their own business ventures participated as respondents in this research. This study adopts a quantitative research approach, employing a questionnaire with Likert-scale items for data collection. The data analysis technique utilized in this research is path analysis, with the support of SPSS 26 software and the Sobel Test. Partially, the findings indicate that entrepreneurship knowledge and family support exert a direct and significant impact on entrepreneurial motivation and the interest in becoming young entrepreneurs among the alumni of the Faculty of Economics at UKI Toraja. Entrepreneurial motivation has a direct and significant influence on the interest in becoming young entrepreneurs among the alumni of the Faculty of Economics at UKI Toraja. Entrepreneurship knowledge has an indirect and significant influence on the interest in becoming a young entrepreneur through entrepreneurial motivation among the alumni of the Faculty of Economics at UKI Toraja. Similarly, family support also has an indirect and significant influence on the interest in becoming a young entrepreneur through entrepreneurial motivation among the alumni of the Faculty of Economics at UKI Toraja